Chimtou, Tunesien: Die Abschlusspublikation eines umfangreichen Münzfundes aus dem tunesischen Chimtou - Nollé, Johannes (e-Forschungsberichte des DAI, 2023)
During excavation work for a new museum in Chimtou (ancient Simitthus)/ Tunesia a hoard of 1,648 late antique solidi was found weighing up to 7.3 kg. In the following years, Hans Roland Baldus (Kommission für Alte Geschichte und Epigraphik des DAI) and his Tunesian colleague Mustapha Khanoussi (Institut National du Patrimoine) studied this huge treasure by compiling a catalogue and trying to shed light on the question when this hoard was buried and why this happened. They also investigated the background of a number of very interesting coins and discussed the question what this hoard tells us about the circulation of gold coins in late antique North Africa. In the end of 2014 their research results were published in volume IV of the Simitthus series.